Kościół pod wezwaniem św. Rafała w Aleksandrowie Łódzkim w latach 1817-1939. Zarys monografii - Wróbel, Robert (Acta Universitatis Lodziensis. Folia Historica, 2002)
The Roman catholic church of St. Raphael in Aleksandrów Łódzki was built in the years 1817-1818 under inspiration of Rafal Bratoszewski, who was then the owner of the settlement. Some selected solutions in the inside (cut comers of nave, stair case behind high altar, oratory around chancel) and composition of the facade (rounded niche at the axis flanked by pairs of Tuscany pillars) mąkę it possible to assign this little church to a well known Warsaw architect Hilary Szpilowski. This building functioned in its primer shape for almost 100 years until the year 1914 when there were some attempts of enlarging started. Stefan Szyller designed new chancel and two vast chapels. Unfortunately those plans were stopped by the outbreak of the First World War. Finally in the years 1923-1926 this idea become realised: following the project of Józef Kaban two aisles were joined to the main corpse and new chancel together with treasure and sacristy were built. Further changes in the corpse of the indicated by parson Witold Nadolski in the years 1933-1934 consisted of redecoration of the facade: two newly built lowers and volute endings over the side naves make it look like pseudo-baroque church. At the same time some important changes were introduced inside: reconstruction of the high altar, adding two new side altars and pictorial decoration of the walls of main nave. New galleries over side naves were also planned but the beginning of Second World War put an end to the works. Although some famous and well-known architects are connected with the church it bears no signs of original, superb architecture. The building belongs to the numerous group of churches that are constantly changed with the time-due to changing needs and preferences.